Orthodontic Forces Induce the Cytoprotective Enzyme Heme Oxygenase-1 in Rats - Suttorp, Christiaan M.; Xie, Rui; Lundvig, Ditte M. S.; Kuijpers-Jagtman, Anne Marie; Uijttenboogaart, Jasper Tom; Van Rheden, René; Maltha, Jaap C.; Wagener, Frank A. D. T. G. (Frontiers in Physiology, 2016)
Orthodontic forces disturb the microenvironment of the periodontal ligament (PDL), and induce craniofacial bone remodeling which is necessary for tooth movement. Unfortunately, orthodontic tooth movement is often hampered by ischemic injury and cell death within the PDL (hyalinization) and root resorption. Large inter-individual differences in hyalinization and root resorption have been observed, and may be explained by differential protection against hyalization. Heme oxygenase-1 (HO-1) forms an important protective mechanism by breaking down heme into the strong anti-oxidants biliverdin/bilirubin and the signaling molecule carbon monoxide. These versatile HO-products protect against ischemic and inflammatory injury. We postulate that orthodontic forces induce HO-1 expression in the PDL during experimental tooth movement. Twenty-five 6-week-old male Wistar rats were used in this study. The upper three molars at one side were moved mesially using a Ni-Ti 10 cN coil spring. The contralateral side served as control. After 6, 12, 72, 96 and 120 hrs rats were killed. On parasagittal sections immunohistochemical staining was performed for analysis of HO-1 expression and quantification of multinuclear osteoclasts. Orthodontic force induced a significant time-dependent HO-1 expression in the mononuclear cell population within the PDL at both the apposition- and resorption side. Shortly after appliance placement HO-1 expression was highly induced in PDL cells but dropped to control levels within 72 hours. Some osteoclasts were HO-1 positive but this induction was shown to be independent of time- and mechanical stress. It is tempting to speculate that differential induction of cytoprotective enzymes as HO-1 in the PDL determines the level of hyalinization and, subsequently, “fast” and “slow” tooth movers during orthodontic treatment.